1999
DOI: 10.1093/humrep/14.5.1234
|View full text |Cite
|
Sign up to set email alerts
|

Case Report:Laparoscopic management of an ectopic pregnancy in a previous Caesarean section scar

Abstract: A case of laparoscopic management of an ectopic pregnancy in a previous Caesarean section scar is reported. A 30 year old woman was admitted to our hospital for profuse vaginal bleeding 2 weeks after an abortion had been performed. A urine pregnancy test was positive. Abdominal ultrasound revealed a well-encapsulated bulging mass over the lower anterior uterine wall measuring 7x5 cm. Hysteroscopy revealed retained gestational tissue in the lower corpus despite a normal uterine cavity. An incision was made over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
0
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 7 publications
1
98
0
8
Order By: Relevance
“…Successful laparoscopic resection of scar pregnancy was first performed by Lee et al [14] Principles of laparoscopic surgery are: scar pregnancy is excised and removed in endobag, bleeding is minimized by local injection of vasopressin, haemostasis is achieved by bipolar diathermy, and the uterine defect is closed by endoscopic suturing. Laparoscopic approach is more justifiable when scar pregnancy is deeply implanted and grows towards abdominal cavity and bladder.…”
Section: Managementmentioning
confidence: 99%
“…Successful laparoscopic resection of scar pregnancy was first performed by Lee et al [14] Principles of laparoscopic surgery are: scar pregnancy is excised and removed in endobag, bleeding is minimized by local injection of vasopressin, haemostasis is achieved by bipolar diathermy, and the uterine defect is closed by endoscopic suturing. Laparoscopic approach is more justifiable when scar pregnancy is deeply implanted and grows towards abdominal cavity and bladder.…”
Section: Managementmentioning
confidence: 99%
“…This is still the preferred option in haemodynamically unstable women when uterine rupture is confirmed or suspected. Laparoscopic removal was later described in 1999 by Lee et al [9] and is most suitable for deeply implanted CSEPs growing toward the abdominal cavity and bladder. For CSEPs growing inwards toward the uterine cavity, hysteroscopic evacuation is most appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other authors [22] suggested that dilatation and curettage is contraindicated for this kind of ectopic pregnancy, since they are considered as cause of uterine perforation and intractable bleeding and consequently, hysterectomy.…”
Section: Discussionmentioning
confidence: 99%